THE CONTROL OF INCIPIENT STATE TREATING TOOL WEAR WITH USAGE OF ACOUSTIC EMISSION - Filonenko, Sergii; Zaritskyi, Oleg (Proceedings of National Aviation University (archive), 2017)
Purpose: The aim of this article is the experimental research of acoustic emission at composite material machining with the analysis of influencing treating tool wear from composite material on registered signals parameters. Methods: In the basis of researches lies the processing and analysis of interconnection experimental acoustic emission signals parameter, which one appear at composite material machining, with treating tool wear. The acoustic emission at initial and final stage of composite material machining are esteemed. The statistical processing of acoustic emission amplitude parameters on these stages was conducted. The statistical data processing with the analysis regularity change of acoustic emission signals amplitudes distribution kurtosis is conducted. Results: Is determined, that the increase of composite material machining time does not result in change of acoustic radiation nature. The registered acoustic emission signals are continuous signals. Is established, that at composite material machining final stage is watched decreasing of acoustic emission signal amplitude average level and value of its deviation. Is determined, that the gradual or instantaneous increase of treating tool wear results in its destruction and sharp decreasing of acoustic emission signal amplitude. The regularity change of acoustic emission signals amplitudes distribution kurtosis at all stages of composite material machining is established. Discussion: The analysis of acoustic emission statistical amplitude parameters change at initial and final stage composite material machining is conducted. Decreasing of acoustic emission statistical amplitude parameters at final stage of machining is shown, that is conditioned by treating tool wear. It is shown, that originating and development of treating tool wearing up to an instant of its damage results in minor decreasing of acoustic emission signal amplitude average level. At the same, at early stage, which one will precede to tool damage, there is a discontinuous of acoustic emission signals amplitudes distribution kurtosis change from stable positive value up to negative value. At the moment of tool disastrous damage the nature of acoustic emission signals amplitudes distribution kurtosis change varies on inverse. Such change of acoustic emission parameters, apparently, is conditioned by originating the processes leading to tool destruction, and, as a consequent, change of treating and treated composite materials conditions interplay. The obtained outcomes have shown that the processing and analysis of regularity of acoustic emission signals amplitudes distribution kurtosis change can be utilized for control of composite materials technological process machining. Thus it is possible to determine and control the moment of processes originating incipient state, which one conduct to destruction of the treating tool.